Novel Approach for Intrusion Detection Using Back Propagation Algorithm - Singh, D.K; Shrivastava, M (International Journal of Computer Sciences and Engineering, 2025)
Intruders are available anywhere. They want to take the benefits of the hidden or confidential information of the user. They are trying access by the different – different techniques. Intruder finding is a big problem at the current time. So that security is important to secure our system or confidential information of any organization. Intrusion Detection System (IDS) is a popular technique for finding intruders that will be available on a network. We will use the KDD CUP 99 dataset for the training purpose of the Back Propagation based IDS model. BPN is an algorithm of the artificial neural network. KDD CUP 99 dataset are authentic dataset for the intruders. This data set will be collected by the UCI Repository